Dental impression materials and combined impression materials

JP7943775B2Active Publication Date: 2026-10-30GC R&D CORP JP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022138667
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-08-31
Publication Date
2026-10-30
Estimated Expiration
2042-08-31

AI Technical Summary

Benefits of technology

【0008】 本発明の一態様によれば、操作性に優れ、歯面への付着を防止する歯科用印象材を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007943775000001
    Figure 0007943775000001
  • Figure 0007943775000002
    Figure 0007943775000002
  • Figure 0007943775000003
    Figure 0007943775000003
Patent Text Reader

Abstract

To provide a dental impression material that is excellent in operability and prevents adhesion to tooth surfaces.SOLUTION: A dental impression material includes: a base material paste that includes alginate and water; and a curing material paste that includes a gelling reagent and a poorly water-soluble liquid compound. The viscosity of 10% aqueous solution of the alginate at 20°C is 5 mPa s or more and 90 mPa s or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a dental impression material and a combined impression material.

Background Art

[0002] In dentistry, a combined impression method is used as a method for taking an intraoral impression when producing a prosthesis. The combined impression method is a method of applying a first impression material with high fluidity to a tooth, then applying a second impression material with low fluidity, bonding the first impression material and the second impression material to each other to combine them, and taking an impression with high accuracy.

[0003] Conventionally, as a combined impression method, an agar-alginate combined impression method is known (for example, refer to Patent Document 1). In the agar-alginate combined impression method, an agar impression material with high fluidity and an alginate impression material with low fluidity are used as the combined impression material.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0005] However, since the fluidity of the agar impression material depends on temperature, complicated operations such as heating for dissolution, heat retention, and temperature adjustment are indispensable, which poses a problem of low handleability.

[0006] An object of the present invention is to provide a dental impression material that is excellent in handleability and prevents adhesion to tooth surfaces.

Means for Solving the Problems

[0007] One aspect of the present invention is a dental impression material comprising a main paste containing an alginate and water, and a curing paste containing a gelling agent and a poorly water-soluble liquid compound, wherein the alginate is a first alginate having a viscosity of 5 mPa·s or more and 90 mPa·s or less in a 10% aqueous solution at 20°C, The viscosity of a 10% aqueous solution at 20°C is 95 mPa·s or higher, 700 mPa·s or lower This is a dental impression material containing a secondary alginate. [Effects of the Invention]

[0008] According to one aspect of the present invention, a dental impression material that is easy to handle and prevents adhesion to the tooth surface can be provided. [Modes for carrying out the invention]

[0009] The following describes embodiments for carrying out the present invention.

[0010] <Dental impression material> The dental impression material of this embodiment is used in the combined impression method. For example, the dental impression material of this embodiment can be used in combination with another alginate impression material to perform a combined impression.

[0011] The dental impression material of this embodiment comprises a main paste and a hardening paste. In this specification, the main paste is a paste-like base material. The hardening paste is a material mixed with the main paste to harden the dental impression material.

[0012] [Main ingredient paste] The main paste contains alginate and water.

[0013] The alginate is composed of an alginate (hereinafter referred to as the first alginate) whose viscosity in a 10% aqueous solution at 20°C is 5 mPa·s or more and 90 mPa·s or less. The viscosity of a 10% aqueous solution of the first alginate at 20°C is preferably 10 mPa·s or more and 70 mPa·s or less, more preferably 20 mPa·s or more and 50 mPa·s or less.

[0014] If the viscosity of a 10% aqueous solution of the first alginate at 20°C is 5 mPa·s or higher, the viscosity of the main paste will not decrease too much, thus preventing a decrease in the operability of the dental impression material. Furthermore, if the viscosity of a 10% aqueous solution of the alginate at 20°C is 90 mPa·s or lower, the fluidity of the mixture of the main paste and the hardening agent paste will increase, improving the accuracy of the impression when the dental impression material of this embodiment is combined with another alginate impression material to perform a combined impression.

[0015] Examples of the first alginate include alkali metal alginates such as sodium alginate and potassium alginate, and ammonium alginates such as ammonium alginate and triethanolamine alginate. Two or more types may be used in combination. Among these, alkali metal alginates are preferred in terms of availability, ease of handling, and the physical properties of the hardened dental impression material, with sodium alginate and potassium alginate being more preferred.

[0016] The content of the first alginate in the main paste is preferably 1% by mass or more and 20% by mass or less, more preferably 3% by mass or more and 15% by mass or less, and even more preferably 5% by mass or more and 10% by mass or less.

[0017] If the content of primary alginate in the main paste is 1% by mass or more, the alginate content in the main paste can be increased while suppressing an increase in viscosity, thus preventing adhesion to the tooth surface while maintaining the operability of the dental impression material. On the other hand, if the content of primary alginate is 20% by mass or less, the viscosity of the dental impression material does not become too high, thus preventing a decrease in impression accuracy when the dental impression material is combined with another alginate impression material for a combined impression.

[0018] The viscosity of a 1% aqueous solution of the primary alginate at 20°C is preferably 2 mPa·s or less, more preferably 1.5 mPa·s or less, and even more preferably 1 mPa·s or less.

[0019] When the viscosity of a 1% aqueous solution of the first alginate at 20°C is 2 mPa·s or less, even if the amount of alginate contained in the dental impression material is increased, an increase in the viscosity of the dental impression material is reliably suppressed, so that adhesion to the tooth surface can be inhibited while preventing a reduction in impression accuracy.

[0020] The lower limit of the viscosity of the 1% aqueous solution of the first alginate at 20°C is not limited, but from the viewpoint of preventing a reduction in impression accuracy due to the excessively low viscosity of the dental impression material, it is preferably 0.1 mPa·s or more.

[0021] The present embodiment may contain an alginate different from the above-mentioned first alginate (hereinafter referred to as the second alginate).

[0022] As for the second alginate, the viscosity of a 10% aqueous solution at 20°C is preferably more than 90 mPa·s and 1000 mPa·s or less, more preferably 95 mPa·s or more and 700 mPa·s or less, and still more preferably 100 mPa·s or more and 500 mPa·s or less.

[0023] When the viscosity of the 10% aqueous solution of the second alginate at 20°C exceeds 90 mPa·s, the impression is less likely to be damaged when the dental impression material is combined with another alginate impression material for a combined impression. In addition, when the viscosity of the 10% aqueous solution of the second alginate at 20°C is 1000 mPa·s or less, the fluidity of the mixture of the base material paste and the curing material paste increases, so that the impression accuracy is improved when the dental impression material of the present embodiment is combined with another alginate impression material for a combined impression.

[0024] Examples of the second alginate include alkali metal alginates such as sodium alginate and potassium alginate, and ammonium alginates such as ammonium alginate and triethanolamine alginate. Two or more of these may be used in combination. Among them, alkali metal alginates are preferred from the viewpoints of easy availability, easy handling, and physical properties of the cured product of the dental impression material, and sodium alginate and potassium alginate are more preferred.

[0025] The content of the second alginate in the main material paste is preferably 1 mass% or more and 20 mass% or less, more preferably 3 mass% or more and 15 mass% or less, and still more preferably 5 mass% or more and 10 mass% or less.

[0026] When the content of the second alginate in the main material paste is 1 mass% or more, the fluidity will not be excessively low when the dental impression material of the present embodiment is combined with another alginate impression material for a combined impression, so that the impression accuracy is improved. On the other hand, when the content of the second alginate in the main material paste is 20 mass% or less, the fluidity will not be excessively high when the dental impression material of the present embodiment is combined with another alginate impression material for a combined impression, so that the impression accuracy is improved.

[0027] The content ratio of the second alginate to the first alginate is preferably 0.4 or more and 2.0 or less by mass ratio, more preferably 0.5 or more and 1.9 or less, and even more preferably 0.6 or more and 1.8 or less. When the content ratio of the second alginate to the first alginate is 0.4 or more and 2.0 or less by mass ratio, adhesion of the dental impression material to the tooth surface can be suppressed while inhibiting a decrease in fluidity of the kneaded product of the main material paste and the curing material paste.

[0028] The total content of all alginates (the first alginate and the second alginate) in the main material paste is preferably 6 mass% or more and 20 mass% or less, more preferably 8 mass% or more and 18 mass% or less, and still more preferably 10 mass% or more and 16 mass% or less.

[0029] If the total alginate content in the main paste is 6% by mass or more, the alginate content in the dental impression material is high, making it less likely for the impression to be damaged when combined with another alginate impression material for a combined impression, and also making it less likely for the hardened dental impression material to adhere to the tooth surface. On the other hand, if the total alginate content in the main paste is 20% by mass or less, the alginate content in the dental impression material does not become too high when combined with another alginate impression material for a combined impression, thus improving the accuracy of the impression.

[0030] For example, ion-exchanged water or distilled water can be used as the water, and water that has been sterilized with sodium hypochlorite or the like may also be used.

[0031] The water content in the main paste is preferably 70% by mass or more and 99% by mass or less, more preferably 75% by mass or more and 95% by mass or less, and even more preferably 80% by mass or more and 90% by mass or less.

[0032] The water content in the dental impression material of this embodiment is preferably 35% by mass or more and 90% by mass or less, more preferably 40% by mass or more and 80% by mass or less. More preferably 55% by mass or more and 75% by mass or less, and even more preferably 45% by mass or more and 70% by mass or less.

[0033] The main paste material preferably further contains a hardening retarder or the like. This increases the working time of the dental impression material in this embodiment.

[0034] Examples of curing retarders include phosphates such as trisodium phosphate and tripotassium phosphate, and condensed phosphates such as sodium pyrophosphate and potassium pyrophosphate, and two or more may be used in combination.

[0035] The content of the curing retarder in the main paste is preferably 0.01% by mass or more and 10% by mass or less, more preferably 0.05% by mass or more and 5% by mass or less, and even more preferably 0.1% by mass or more and 3% by mass or less.

[0036] If the hardening retardant content in the main paste is 0.01% by mass or more, the working time of the dental impression material of this embodiment becomes longer, and if it is 10% by mass or less, the initial hardening time of the dental impression material of this embodiment becomes shorter, and the strength of the hardened body of the dental impression material of this embodiment is improved.

[0037] The main paste may further contain fillers, colorants, preservatives, disinfectants, fragrances, pH adjusters, surfactants, etc.

[0038] The consistency of the main paste is preferably 30 mm or more. When the consistency of the main paste is 30 mm or more, the fluidity of the mixture of the main paste and the hardening agent paste increases. Therefore, when the dental impression material of this embodiment is combined with another alginate impression material to perform a combined impression, the accuracy of the impression is improved.

[0039] [Hardening agent paste] The hardening agent paste contains a gelling reagent and a poorly water-soluble liquid compound.

[0040] As the gelling agent, a compound of a metal with a valency of 2 or higher can be used.

[0041] Examples of compounds of metals with a valency of 2 or higher include salts, oxides, and hydroxides of metals with a valency of 2 or higher, and two or more of these may be used in combination.

[0042] Examples of metals with a valence of 2 or higher include calcium, magnesium, zinc, aluminum, iron, titanium, zirconium, and tin.

[0043] Examples of salts of metals with a valency of 2 or higher include calcium sulfate dihydrate (CaSO4·2H2O), calcium sulfate hemihydrate (CaSO4·1 / 2H2O), and anhydrous calcium sulfate (CaSO4).

[0044] Examples of oxides of metals with a valency of 2 or higher include calcium oxide, magnesium oxide, zinc oxide, titanium oxide, zirconium oxide, and tin oxide.

[0045] Examples of hydroxides of metals with a valency of 2 or higher include calcium hydroxide, magnesium hydroxide, zinc hydroxide, aluminum hydroxide, and iron hydroxide.

[0046] The gelling agent content in the hardening paste is preferably 10% by mass or more and 60% by mass or less. If the gelling agent content in the hardening paste is 10% by mass or more, the strength of the hardened body of the dental impression material of this embodiment is improved, and if it is 60% by mass or less, the working time of the dental impression material of this embodiment is extended.

[0047] The poorly water-soluble liquid compound is not particularly limited as long as it can be pasteurized into a gelling agent, but examples include hydrocarbon compounds, aliphatic alcohols, aromatic alcohols, fatty acids, fatty acid esters, silicone oils, etc. Two or more of these may be used in combination.

[0048] In this specification, "poorly water-soluble" means that the solubility in 100g of water at 20°C is 5g or less.

[0049] The hydrocarbon compound may be either a chain compound or a cyclic compound.

[0050] Examples of hydrocarbon compounds include hexane, heptane, octane, nonane, decane, undecane, dodecane, tridecane, tetradecane, pentadecane, 2,7-dimethyloctane, 1-octene, cycloheptane, cyclononane, kerosene, and liquid paraffin.

[0051] The aliphatic alcohol may be either a saturated aliphatic alcohol or an unsaturated aliphatic alcohol.

[0052] Examples of aliphatic alcohols include 1-hexanol, 1-octanol, citronellol, and oleyl alcohol.

[0053] Examples of aromatic alcohols include benzyl alcohol and m-cresol.

[0054] The fatty acids may be either saturated or unsaturated fatty acids.

[0055] Examples of fatty acids include hexanoic acid, octanoic acid, oleic acid, and linoleic acid.

[0056] The fatty acid ester may be either a saturated fatty acid ester or an unsaturated fatty acid ester.

[0057] Examples of fatty acid esters include ethyl octanoate, butyl phthalate, glyceride oleate, olive oil, sesame oil, liver oil, and whale oil.

[0058] Examples of silicone oils include polydimethylsiloxane, polymethylphenylsiloxane, polymethylhydrogensiloxane, and polyphenylhydrogensiloxane.

[0059] The content of poorly water-soluble liquid compounds in the hardening paste is preferably 10% by mass or more and 50% by mass or less, and more preferably 15% by mass or more and 30% by mass or less. When the content of poorly water-soluble liquid compounds in the hardening paste is 10% by mass or more, the operability of the dental impression material of this embodiment is improved, and when it is 50% by mass or less, the strength of the hardened body of the dental impression material of this embodiment is improved.

[0060] The hardening paste preferably further contains polybutene. This improves the hardening properties of the dental impression material of this embodiment and also increases the working time of the dental impression material of this embodiment.

[0061] Polybutene is preferably in liquid form.

[0062] Polybutene can be synthesized by copolymerizing isobutene and 1-butene.

[0063] The number-average molecular weight of polybutene is preferably between 300 and 4000.

[0064] The polybutene content in the hardening paste is preferably 0.5% by mass or more and 30% by mass or less, and more preferably 1% by mass or more and 20% by mass or less. When the polybutene content in the hardening paste is 0.5% by mass or more and 30% by mass or less, the operability of the dental impression material of this embodiment is improved.

[0065] The hardening paste preferably further contains a hardening retarder. This extends the working time of the dental impression material in this embodiment.

[0066] Examples of curing retarders include phosphates such as trisodium phosphate and tripotassium phosphate, and condensed phosphates such as sodium pyrophosphate and potassium pyrophosphate, and two or more may be used in combination.

[0067] The content of the hardening retarder in the hardening paste is preferably 0.01% by mass or more and 10% by mass or less. If the content of the hardening retarder in the hardening paste is 0.01% by mass or more, the working time of the dental impression material of this embodiment will be longer, and if it is 10% by mass or less, the initial hardening time of the dental impression material of this embodiment will be shorter and the strength of the hardened body of the dental impression material of this embodiment will be improved.

[0068] The hardening paste may further contain fillers, hardening modifiers, surfactants, colorants, preservatives, disinfectants, fragrances, pH adjusters, etc.

[0069] Examples of materials that make up the filler include clay minerals such as diatomaceous earth, talc, and smectite, and inorganic oxides such as silica and alumina, and two or more of these may be used in combination.

[0070] Examples of curing modifiers include potassium titanium fluoride and potassium silica fluoride, and two or more may be used in combination.

[0071] Examples of surfactants include polyoxyethylene alkyl ethers, and two or more types may be used in combination.

[0072] The consistency of the hardening agent paste is preferably 30 mm or more. When the consistency of the hardening agent paste is 30 mm or more, the fluidity of the mixture of the main paste and the hardening agent paste increases. Therefore, when the dental impression material of this embodiment is combined with another alginate impression material to perform a combined impression, the accuracy of the impression is improved.

[0073] The consistency of the mixture of the main paste and the hardening agent paste is 36 mm or more, preferably 38 mm or more. When the consistency of the mixture of the main paste and the hardening agent paste is 36 mm or more, the fluidity of the mixture of the main paste and the hardening agent paste increases. Therefore, when the dental impression material of this embodiment is used in combination with another alginate impression material to perform a combined impression, the accuracy of the impression is improved.

[0074] The upper limit of the consistency of the mixture of the main paste and the hardening agent paste is not particularly limited, but is usually 50 mm.

[0075] The method for measuring the consistency of the mixture of the main paste and the hardener paste is as follows: The main paste and the hardener paste are mixed by hand at a temperature of 23°C ± 2°C until uniform, and then 0.5 ± 0.2 ml of the mixture is placed on a glass plate. Next, 30 seconds after starting to mix the main paste and the hardener paste, a weight is placed on top so that the total weight including the glass plate is 500 g. Next, 5 seconds after placing the weight, the weight is removed, and the dimensions of the maximum and minimum points between the parallel cleats of the spread mixture are measured in 0.5 mm units. Next, the average value of the dimensions of the maximum and minimum points between the parallel cleats of the spread mixture is calculated and taken as the consistency of the paste.

[0076] [How to use dental impression material] The dental impression material of this embodiment is used by mixing a main paste and a hardening paste.

[0077] For example, a manual or electric extruder is used to extrude the main paste and hardener paste, which are filled in separate packaging containers, and the resulting mixture, which is then mixed as it passes through a nozzle, is applied to the teeth.

[0078] Examples of packaging containers include molded products made of resin or metal, bags made of resin or metal, and so on.

[0079] When mixing the hardening agent paste and the main agent paste, the mass ratio of the main agent paste to the hardening agent paste is preferably 1 or more and 5 or less.

[0080] As a result of diligent research, the inventors discovered that increasing the content of alginate impression material in the main paste that constitutes dental impression material has the effect of preventing the dental impression material from adhering to the tooth surface. On the other hand, increasing the content of alginate impression material in the main paste makes the viscosity of the main paste too high, making it impossible to mix the main paste and the hardening agent paste.

[0081] In contrast, in this embodiment, as described above, the main paste contains an alginate (first alginate) with a viscosity of 5 mPa·s or more and 90 mPa·s or less at 20°C in a 10% aqueous solution. This suppresses the increase in viscosity of the dental impression material even when the amount of alginate contained in the dental impression material is increased, and allows for mixing of the main paste and the hardening agent paste. Therefore, the dental impression material of this embodiment offers excellent operability, and by performing a combined impression in combination with another alginate impression material, it is possible to obtain a highly accurate impression and prevent adhesion to the tooth surface.

[0082] Furthermore, in this embodiment, as described above, the viscosity of a 1% aqueous solution of the first alginate at 20°C is 2 mPa·s or less, so even if the amount of alginate contained in the dental impression material is increased, the increase in the viscosity of the dental impression material can be reliably suppressed. Therefore, the dental impression material of this embodiment has superior operability, and by performing a combined impression in combination with another alginate impression material, it is possible to obtain a more accurate impression and reliably prevent adhesion to the tooth surface.

[0083] <Combined impression material> The combined impression material of this embodiment comprises the dental impression material of this embodiment and an alginate impression material. That is, the dental impression material of this embodiment is applicable for combined impressions.

[0084] The alginate impression material is not particularly limited, but for example, an alginate impression material used in the agar-alginate combined impression method can be used.

[0085] The alginate impression material may be in powder form, or it may be in paste form, comprising alginate, a main paste containing water, a gelling agent, and a curing paste containing a poorly water-soluble liquid compound.

[0086] Here, the paste-type alginate impression material is the same as the dental impression material of this embodiment, except that the alginate contained in the main paste is an alginate whose viscosity in a 10% aqueous solution at 20°C is 5 mPa·s or more and 90 mPa·s or less.

[0087] Using the combined impression material of this embodiment, it is possible to obtain an impression of teeth.

[0088] For example, after applying the dental impression material of this embodiment to a tooth, an alginate impression material is applied to the tooth to which the dental impression material of this embodiment has been applied.

[0089] In the combined impression material of this embodiment, as described above, the same effect as the dental impression material of this embodiment can be obtained by having a different alginate impression material (applying the dental impression material of this embodiment as a combined impression material). In this specification, "a different alginate impression material" refers to an alginate impression material different from the dental impression material of this embodiment.

[0090] In other words, in the combined impression material of this embodiment, the main paste constituting the dental impression material contains an alginate (first alginate) with a viscosity of 5 mPa·s to 90 mPa·s at 20°C in a 10% aqueous solution. Therefore, even if the amount of alginate contained in the dental impression material is increased, the increase in the viscosity of the dental impression material is suppressed, and mixing of the main paste and the hardening agent paste becomes possible. As a result, the combined impression material of this embodiment offers excellent handling of the dental impression material, makes it possible to obtain highly accurate impressions by combining it with other alginate impression materials, and prevents adhesion to the tooth surface. [Examples]

[0091] The following describes examples of the present invention, but the present invention is not limited to these examples. The examples and comparative examples were evaluated by the following tests. In the following, unitless values ​​are based on mass (parts by mass or mass%) unless otherwise specified.

[0092] <Preparation of hardening agent paste> A curing paste was obtained by mixing 45 parts by mass of anhydrous calcium sulfate (CaSO4), 6 parts by mass of magnesium hydroxide, 2 parts by mass of zinc oxide, 23 parts by mass of liquid paraffin, 4 parts by mass of polybutene, 1.5 parts by mass of tripotassium phosphate, 12.5 parts by mass of silica, 3 parts by mass of potassium titanium fluoride, and 3 parts by mass of polyoxyethylene alkyl ether.

[0093] <Preparation of the main paste> The main paste was obtained by mixing an alkali metal salt of alginic acid, water, and sodium pyrophosphate in the proportions shown in Table 1 [parts by mass].

[0094] Details of the alkali metal salts of alginate are shown below.

[0095] [First-order alginate] Sodium alginate ULV-L3G (manufactured by Kimika): Viscosity of 10% aqueous solution at 20℃: 20-50 mPa·s, viscosity of 1% aqueous solution: 0.6 mPa·s) • Potassium alginate K-ULV-L3G (manufactured by Kimika): Viscosity of 10% aqueous solution at 20℃: 20-50 mPa·s, viscosity of 1% aqueous solution: 0.5 mPa·s)

[0096] [Second alginate] • Potassium alginate K-1G (manufactured by Kimika): 1% aqueous solution viscosity 100-200 mPa·s at 20℃. • Sodium alginate I-3G (manufactured by Kimika): 1% aqueous solution at 20°C, viscosity 300-400 mPa·s)

[0097] [Adhesion] A cross-section of a bovine tooth embedded in acrylic resin was polished with #600 grit waterproof abrasive paper. A mixture of hardener paste and main material paste was prepared by mixing them in a mass ratio of 1:2 under conditions of 23°C ± 2°C. 1.5 mL of this mixture was extruded onto the surface of the polished bovine tooth cross-section, and a test specimen was prepared by pressing it with an acrylic plate. This test specimen was placed in a 35°C constant temperature water bath to harden the mixture of dental impression material. The test specimen was removed, and the acrylic plate and the specimen were peeled off the bovine tooth for surface observation. The results are shown in Tables 1-3.

[0098] [Evaluation Criteria] Excellent: Does not adhere completely Good: Slightly attached Not possible: Completely attached

[0099] <Mixability with hardening agent paste> Under conditions of 23°C ± 2°C, a hardening agent paste and a main material paste were filled into a cartridge in a mass ratio of 1:2. The mixed dental impression material (mixed paste) was then extruded from the cartridge, and the mixed paste was visually observed. The results are shown in Tables 1-3.

[0100] [Evaluation Criteria] Excellent: Evenly blended Good: Can be mixed, but unevenness remains. Impossible: Mixing is not possible.

[0101] <Consistency> Under conditions of 23℃±2℃, the hardening agent paste and the main material paste were mixed in a mass ratio of 1:2. Then, 0.5±0.2 ml of the mixture was placed on a glass plate. Next, 25 seconds after the start of mixing the main material paste and hardening agent paste, a weight was placed on the glass plate so that the combined load was 14.71±0.01 N. Next, 5 seconds after the weight was placed, the weight was removed, and the dimensions of the maximum and minimum points between the parallel cleats of the spread mixture were measured in units, and the average value was calculated. The consistency test was performed only for Examples 1, 2, 8, 9, and Comparative Examples 2 and 3. The results are shown in Tables 1 and 3.

[0102] [Evaluation Criteria] Excellent: Consistency is 38mm or more Good: Consistency between 36mm and 38mm Unacceptable: Consistency less than 36 mm

[0103] [Table 1]

[0104] [Table 2]

[0105] [Table 3]

[0106] Tables 1-3 show that all test specimens (Examples 1-13) containing alginate with a viscosity of 5 mPa·s to 90 mPa·s at 20°C in a 10% aqueous solution had good adhesion and mixing properties with the hardening agent paste. Furthermore, some test specimens (Examples 1, 2, 8, and 9) had good consistency.

[0107] On the other hand, test specimens in which the main paste did not contain an alginate with a viscosity of 5 mPa·s to 90 mPa·s in a 10% aqueous solution at 20°C all exhibited poor adhesion (Comparative Examples 1-4).

[0108] The embodiments disclosed above include, for example, the following aspects: (Note 1) It is a dental impression material, A main paste containing alginate and water, The material comprises a gelling agent and a curing paste containing a poorly water-soluble liquid compound, A dental impression material wherein the viscosity of a 10% aqueous solution of the aforementioned alginate at 20°C is 5 mPa·s or more and 90 mPa·s or less. (Note 2) The dental impression material described in Appendix 1, wherein the viscosity of a 1% aqueous solution of the alginate at 20°C is 2 mPa·s or less. (Note 3) Dental impression material as described in Appendix 1 or 2, for combined impression purposes. (Note 4) Dental impression material as described in any one of the appendices 1 to 3, A combined impression material having another alginate impression material.

[0109] Although embodiments of the present invention have been described above, the present invention is not limited to any particular embodiment, and various modifications and changes are possible within the scope of the invention as described in the claims.

Claims

1. It is a dental impression material, A main paste containing alginate and water, The material comprises a gelling agent and a curing paste containing a poorly water-soluble liquid compound, The alginate is a first alginate whose viscosity in a 10% aqueous solution at 20°C is 5 mPa·s or more and 90 mPa·s or less, A dental impression material comprising a secondary alginate whose viscosity at 20°C in a 10% aqueous solution is 95 mPa·s or more and 700 mPa·s or less.

2. The dental impression material according to claim 1, wherein the viscosity of a 1% aqueous solution of the first alginate at 20°C is 2 mPa·s or less.

3. A dental impression material according to claim 1, for use with combined impressions.

4. A dental impression material according to any one of claims 1 to 3, A combined impression material having another alginate impression material.

Citation Information

Patent Citations

  • Bis dimethylbenzyl diphenylamine antiscorching agent for halogenated phosphoric esterrcontaining polyurethane foam

    JP1981020019A

  • Impression material composition

    JP1988239207A

  • Alginic acid salt impression material composition for dental use

    JP1993017315A

  • Alginate impression material

    JP1998316521A

  • Dental alginate impression material

    JP2014094913A